The Suicidal Intrusions Attributes Scale (SINAS): a new tool measuring suicidal intrusions - van Bentum, Jaël S.; Kerkhof, Ad J. F. M.; Huibers, Marcus J. H.; Holmes, Emily A.; de Geus, Stephan; Sijbrandij, Marit (Frontiers in Psychiatry, 2023)
Introduction Suicidal intrusions are uncontrollable, intrusive mental images (e. g., visualizing a future suicidal act). They may also be called suicidal “flash-forwards.” Despite the importance of integrating the assessment of suicidal intrusions into a clinical routine assessment, quick self-report screening instruments are lacking. This study describes the development of a new instrument—Suicidal Intrusions Attributes Scale (SINAS)—to assess the severity and characteristics of suicidal intrusions and examines its psychometric properties. Method The sample included currently suicidal outpatients with elevated levels of depression recruited across mental health institutions in the Netherlands (N = 168). Instruments administered were 10-item SINAS, the Suicidal Ideation Attributes Scale (SIDAS), the Prospective Imagery Task (PIT), four-item Suicidal Cognitions Interview (SCI), and the Beck Depression Inventory (BDI-II). Results An exploratory factor analysis identified a one-factor structure. The resulting SINAS demonstrated good internal consistency (Cronbach's α = 0.91) and convergent validity, as expected. Discussion Overall, this study demonstrated acceptable levels of reliability and validity of the measure in a depressed clinical population with suicidal ideation. The SINAS may be a useful screening tool for suicidal intrusions in both research and clinical settings.